Síndrome de Mayer-Rokitansky-Kuster-Hauser: comunicación de dos casos - Ayala Céspedes, Darwin (2024)
Mayer-Rokitansky-Küster-Hauser syndrome (SMRKH) is a congenital pathologycharacterized by aplasia or agenesis of structures that develop from the mullerianducts in genotypically and phenotypically normal females. The prevalence of thissyndrome is uncertain. There are only two population-based studies evaluating it. Wepresent two clinical cases, in an adolescent and older adult woman. These patientsrequire clinical, epidemiological, hormonal and imaging studies by a multidisciplinaryteam that includes a psychologist to support the patient’s acceptance of thesituation, as well as considerations related to subsequent surgeries and reproductiveconsequences.